Functional Analysis of the Amino- and Carboxyl-Termini of Streptokinase - Fay, William P.; Bokka, Lakshmi V. (Thrombosis and Haemostasis, 1998)
Streptokinase (SK) is a 414 amino acid bacterial protein that activates human plasminogen. Streptokinase fragments derived from the central portion of the protein bind plasminogen, but are inactive, indicating that the amino- and/or carboxyl-termini are required for normal plasminogen activator activity. To better define the function of the N- and C-termini of SK we generated and characterized 21 N-terminal and 20 C-terminal deletion mutants. All mutants lacking ≥18 N-terminal or ≥51 C-terminal amino acids exhibited markedly reduced plasminogen activator activity, while mutants lacking ≤12 N-terminal or ≤40 C-terminal residues were fully active. The decrease in SK activity with N-terminal deletion appeared to result not from loss of plasminogen binding capacity, but rather from increased susceptibility of deletion mutants to degradation by plasmin. Point mutations at positions 13 (SK V13D) or 20 (SK V20D) produced functional abnormalities similar to those observed in N-terminal deletion mutants, with SK V13D exhibiting delayed amidolytic activity and SK V20D exhibiting only 1% plasminogen activator activity and marked sensitivity to degradation by plasmin. C-terminal deletion mutants lacking ≥51 amino acids also bound plasminogen, but did not induce significant amidolytic activity in plasminogen or activator activity in plasmin. Prevention of cleavage at position 59 of SK had no effect on plasminogen activator activity, suggesting that the rapid hydrolysis of this bond that occurs after SK-plasminogen complex formation is not required for normal function of the N-terminus. These results suggest that residues within or near positions 13-20 of SK are important determinants of its capacity to generate amidolytic activity and are a critical determinant of the stability of SK, while residues within or near position 364-374 are required for generating amidolytic activity and for conferring plasminogen activator activity to plasmin(ogen). These results also suggest that SK fragments significantly smaller than SK 13-374 are unlikely to be effective thrombolytic agents.